Reflections on COVID-19 and the viability of curriculum adjustment and delivery options in the South African educational space - Hosea O. Patrick; Rhoda T.I. Abiolu; Oluremi A. Abiolu (Transformation in Higher Education, 2021)
Background: The coronavirus disease (COVID-19) pandemic brought unprecedented changes leading to ‘business unusual’ in all facets of life and livelihood on a global scale. The restrictions on gathering, social distancing and lockdown measures necessitated by the need to curtail its spread, had, and still have an enormous impact on the educational sector as indeed all spheres of life. These measures implied a change in the traditional modus operandi of curriculum and delivery options for educational institutions in South Africa in the bid to continue academic sessions. Hence, a transition of educational institutions from physical interactions to virtual meetings and the need to evolve curriculum contents and delivery.